Associations of suicide risk with emotional reactivity, dysregulation, and eating disorder treatment outcomes. Issue 6 (9th September 2022) - Denning, Dominic M.; Perry, Taylor R.; Reilly, Erin E.; Berner, Laura A.; Velkoff, Elizabeth A.; Kaye, Walter H.; Wierenga, Christina E.; Brown, Tiffany A.
Abstract: Introduction: Emotional processes play a role in both suicide risk and eating disorders (EDs), which are often comorbid. However, limited research has explored how emotional processes relate to suicide risk in EDs and the prognostic value of suicide risk for ED treatment. Thus, the current study examined associations between emotion dysregulation and reactivity with suicide risk in patients with EDs, and determined if suicide risk predicts ED treatment outcomes. Methods: Participants ( n = 201) were adults in an ED partial hospitalization program who completed measures at admission, 1‐month post‐admission, and discharge. Results: When controlling for depressive symptoms, limited access to adaptive emotion regulation strategies, difficulties engaging in goal‐oriented behaviors, and engaging in impulsive behavior when experiencing negative emotions (i.e., emotion dysregulation) were associated with suicide attempt frequency. Depressive symptoms were associated with suicide risk severity, while emotion dysregulation and reactivity were not. Importantly, patients with elevated suicide risk at admission improved comparably to other risk categories across treatment, despite presenting with greater ED symptoms at admission. Conclusion: Emotion dysregulation and depression are salient factors when examining suicide risk in patients with EDs. Suicide risk and attempt history may not negatively impact ED treatment outcomes when using emotion‐focused treatment.